Exploring influencing factors of healthy lifestyles in rural area among older adults with diabetes based on socioecological model - Yudong Miao; Xinran Li; Zhanlei Shen; Dongfang Zhu; Junwen Bai; Jingbao Zhang; Ruizhe Ren; Dan Guo; Clifford Silver Tarimo; Jinxin Cui; Mingyue Zhen; Jiajia Zhang; et al. (Scientific Reports)
Abstract Previous research on lifestyle has primarily focused on individual lifestyle factors, often overlooking the broader influence of social determinants. This study aimed to examine factors associated with healthy lifestyle scores (HLS) among older adults with diabetes, emphasizing modifiable behaviors within the framework of the socioecological model (SEM). A cross-sectional survey was conducted from July 1 to August 31, 2023, in Jia County, Henan Province, utilizing a whole-cluster sampling method. Influencing factors were categorized into five levels based on the socioecological model (SEM). We used Generalized linear models to examine the associations between these factors and HLS, while adjusting for potential confounders. The study included 5,451 eligible participants. The proportion of participants with healthy sleep habits was notably low (14.71%). Higher HLS were positively associated with being female, better cognitive competence, greater social engagement, and unemployment. In contrast, lower HLS were significantly associated with the presence of complications, depression, higher income, and residing farther from major roads. This study identified the key modifiable factors influencing HLS among older adults with diabetes. Disrupted sleep patterns emerged as a significant concern warranting targeted intervention. Medical insurance directly affects the accessibility and economic burden of medical resources. The government should further optimize medical insurance policies to facilitate patients in adopting healthier lifestyles choices.